1,2,3-Triazole derivatives as antitubercular agents: synthesis, biological evaluation and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Nawale, Laxman; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Shingate, Bapurao B. (MedChemComm, 2015)
Searching for new active molecules against Mycobacterium tuberculosis (MTB) H37Ra, a small focused library of 1,2,3-triazoles has been efficiently prepared via a click chemistry approach. The newly synthesized compounds were tested against drug-sensitive MTB. Several derivatives were found to be promising inhibitors of MTB characterized by lower MIC values (5.8-29.9 mu g mL(-1)). Among all the synthesized 31 compounds, 15e was the most active compound against MTB. Based on the results from the antitubercular activity, SAR for the synthesized series has been developed. The active compounds from the anti-tubercular study were further tested for anti-proliferative activity against THP-1, A549 and PANC-1 cell lines using MTT assay and showed no significant cytotoxic activity against these three cell lines except THP-1 at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antioxidant activities with an IC50 range of 10.1-37.3 mu g mL(-1). The molecular docking study of the synthesized compounds was performed against the DprE1 enzyme of MTB to understand the binding interactions. Moreover, the synthesized compounds were also analysed for ADME properties and all the experimental results promote us to consider this series as a starting point for the development of novel and more potent anti-tubercular agents in the future.

[Et3NH][HSO4] catalyzed efficient synthesis of 5-arylidene-rhodanine conjugates and their antitubercular activity - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman; Yeware, Amar; Sarkar, Dhiman; Shingate, Bapurao B. (Research on Chemical Intermediates, 2016)
We have described a highly efficient, safer protocol for the synthesis of 5-arylidene-rhodanine conjugates catalyzed by Bronsted acidic ionic liquid [Et3NH][HSO4] in excellent yields. The protocol offers cost-effective, environmentally benign, solvent-free conditions and recycle-reuse of the catalyst. The synthesized 5-arylidene-rhodanine conjugates were characterized on the basis of (1) H NMR, C-13 NMR and HRMS spectral data. A series of 5-arylidene-rhodanine derivatives 3a-h, 4a-h were synthesized and evaluated for their in vitro antitubercular activity against dormant Mycobacterium tuberculosis H37Ra and M. bovis BCG strains. Moreover, compounds 3a, 3b, 3e, 3f, 3g, 3h and 4f exhibited good antitubercular activity and were also evaluated for anti-proliferative activity against MCF-7, A549 and HCT116 cell lines using modified MTT assay and found to be noncytotoxic. Compounds 3a-h and 4f were further screened for their antibacterial activity against four bacteria strains to assess their selectivity towards M. tuberculosis. Furthermore, in silico ADME prediction of all the tested compounds followed the criteria for orally active drug and, therefore, these compounds may have a good potential for eventual development as oral agents.

Facile synthesis of 1,3-thiazolidin-4-ones as antitubercular agents - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Arkile, Manisha A.; Yeware, Amar; Sarkar, Dhiman; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
We have developed, highly efficient, one-pot, solvent-free, [Et3NH][HSO4] catalyzed multicomponent reaction protocol for the synthesis of 1,3-thiazolidin-4-ones in excellent yields. For the first time, the 1,3-thiazolidin-4-ones were evaluated in vitro for their antimycobacterial activity against Mycobacterium tuberculosis dormant MTB H37Ra and Mycobacterium bovis BCG strains. Among the synthesized basic 1,3-thiazolidin-4-ones, particularly the compounds 4c, 4d, 4e, 4f, 4h, 4i and 4j displays promising antitubercular activity along with no significant cytotoxicity against the cell lines MCF-7, A549 and HCT-116. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Antitubercular; Cytotoxicity; Green protocol; Multicomponent reaction

Facile synthesis of new N-sulfonamidyl-4-thiazolidinone derivatives and their biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Shingate, Bapurao B. (New Journal of Chemistry, 2016)
The one-pot three-component syntheses of new N-sulfonamide-thiazolidin-4-one derivatives were carried out in excellent yield using [HDBU][HSO4] as an ionic liquid under solvent-free conditions. The newly synthesized compounds were screened against fungal strains and a number of compounds were seen to display excellent antifungal activity. In addition, the synthesized compounds were screened for their scavenging activity of the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical and showed very good antioxidant activity. Finally, theoretical predictions derived from molecular docking studies against the potential target sterol 14 alpha-demethylase (CYP51) helped establish a link between the observed biological activity and the binding affinity, thereby providing insights into the specific bonding and non-bonding interactions governing the activity.

Novel tetrazoloquinoline-rhodanine conjugates: highly efficient synthesis and biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman; Yeware, Amar; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and Mycobacterium bovis BCG, a small focused library of rhodanine incorporated tetrazoloquinoline has been efficiently synthesized by using [HDBU][HSO4] acidic ionic liquid. The compound 3c found to be promising inhibitor of MTB H37Ra and M. bovis BCG characterized by lower MIC values 4.5 and 2.0 mu g/mL, respectively. The active compounds were further tested for cytotoxicity against HeLa, THP-1, A549 and PANC-1 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Again, the synthesized compounds were found to have potential antifungal activity. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target Zmp1 enzyme of MTB H37Ra, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of in vitro and in silico study suggest that these compounds possess ideal structural requirement for the further development of novel therapeutic agents. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Antitubercular; Cytotoxicity; Docking study; Rhodanine derivatives

Novel tetrazoloquinoline-thiazolidinone conjugates as possible antitubercular agents: synthesis and molecular docking - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Shingate, Bapurao B.; Nawale, Laxman; Sarkar, Dhiman; Khedkar, Vijay M. (Medchemcomm, 2016)
A novel approach for the synthesis of a new 4-thiazolidinone scaffold was developed by a one-pot three-component cyclocondensation of various tetrazolo quinoline aldehydes 1a-f, acid hydrazide 2a-c, and thioglycolic acid 3 in the presence of [DBUH].OAc] as a catalyst in high yields. All the conjugates were screened for their antimycobacterial activity against MTB H37Ra and M. bovis BCG strains, with the MIC values ranging from 0.99-13.55 mu mol mL(-1) and 0.14-20.11 mu mol mL(-1), respectively. The 4-thiazolidinone-incorporated tetrazoloquinoline derivatives 4a, 4d, 4g, 4j, 4m, and 4p were highly potent against MTB H37Ra and M. bovis BCG strains. The most active compounds were also evaluated for their cytotoxicity against MCF-7, A549, and HCT 116 cell lines and were found to be non-cytotoxic. Further, molecular docking studies into the active site of the InhA enzyme revealed a similar binding mode to the native ligand in the crystal structure, thereby helping us to understand the ligand-protein binding interaction and establish a structural basis for the inhibition of mycobacterium tuberculosis. The results suggest that the tetrazoloquinoline-thiazolidinone conjugates 4a, 4d, 4g, 4j, 4m, and 4p are promising antitubercular agents.

Synthesis and bioactivity of novel triazole incorporated benzothiazinone derivatives as antitubercular and antioxidant agent - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Arkile, Manisha A.; Khedkar, Vijay M.; Jadhav, Nandadeep J.; Sarkar, Dhiman; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and M. bovis BCG, a small focused library of benzothiazinone based 1,2,3-triazoles has been efficiently prepared via click chemistry approach. Several derivatives were found to be promising inhibitors of MTB and M. bovis BCG characterized by lower MIC values (27.34-29.37 mu g/mL). Among all the synthesized compounds, 6c and 6e is the most active compound against MTB and M. bovis BCG. The compounds were further tested for anti-proliferative activity against HeLa, A549 and A431 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antioxidant activity with IC50 range = 14.14-47.11 mu g/mL. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target MTB DprE1, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of the in vitro and in silico study suggest that the triazole incorporated benzothiazinone may possess the ideal structural requirements for further development of novel therapeutic agents. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; ADME prediction; Antioxidant; Antitubercular; Docking study

Synthesis, biological evaluation and molecular docking of novel coumarin incorporated triazoles as antitubercular, antioxidant and antimicrobial agents - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Shingate, Bapurao B.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Nawale, Laxman; Sarkar, Dhiman; Navale, Govinda R.; Shinde, Sandip S. (Medicinal Chemistry Research, 2016)
A series of new coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular activity in vitro against Mycobacterium tuberculosis H37Ra, antioxidant activity by DPPH radical scavenging assay, antimicrobial activity in vitro against three gram-positive bacteria (Staphylococcus aureus, Micrococcus luteus and Bacillus cereus) and three gram-negative bacteria (Escherichia coli, Pseudomonas fluorescens and Flavobacterium devorans as well as three fungi (Aspergillus niger, Penicillium chrysogenum and Curvularia lunata). The bioactive assay showed that some synthesized coumarin triazoles displayed comparable or even better antitubercular, antioxidant, antibacterial and antifungal efficacy in comparison with reference drugs. Furthermore, docking study has been performed against DprE1 enzyme of M. tuberculosis that showed good binding interactions. Moreover, the synthesized compounds were also analyzed for ADME properties and showed potential to build up as good oral drug candidates. New coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular, antioxidant, antibacterial and antifungal activity. Some of the coumarin-based triazole derivatives displayed comparable or even better efficacy in comparison with reference drugs. Molecular docking study has been performed against DprE1 enzyme of Mycobacterium tuberculosis showed good binding interactions. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Antitubercular; Click chemistry; Docking study

Quinolidene based monocarbonyl curcumin analogues as promising antimycobacterial agents: synthesis and molecular docking study - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman U.; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (Bioorganic & medicinal chemistry letters, 2017)
A series of quinoline incorporated monocarbonyl curcumin analogues was efficiently synthesized using [HDBU][HSO4] as catalyst via Knoevenagel type condensation and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis BCG in dormant state. The analogues 3e, 3h, 4a and 4e exhibited very good antitubercular activity. The antiproliferative activity of the analogues against MCF-7, A549 and HCT-116 cell lines was evaluated using modified MTT assay and these compounds were found to be non-cytotoxic. Molecular docking study has been carried out against M. tuberculosis pantothenate synthetase (MTB PS) enzyme in an effort to enhance the understanding of their action as antitubercular agents. The potency, low cytotoxicity and selectivity of these analogues support them as valid leads for further optimization.

Quinolidene-rhodanine conjugates: facile synthesis and biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Shingate, Bapurao B.; Nawale, Laxman; Sarkar, Dhiman; Khedkar, Vijay M.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N. (European Journal of Medicinal Chemistry, 2017)
A series of rhodanine incorporated quinoline derivatives were efficiently synthesized using reusable DBU acetate as ionic liquid and evaluated for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB) (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743) both in active and dormant state. Compounds 3e, 3f, 3g, 3h and 3i exhibited very good antitubercular activity. The active compounds were studied for cytotoxicity against HUVEC, THP-1, macrophages, A549, PANC-1 and HeLa cell lines using modified MTT assay and were found to be noncytotoxic. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity towards the MTB. Further, the synthesized compounds have been screened for their in vitro antifungal activity. In addition, the molecular docking studies revealed the binding modes of these compounds in active site of Zmp1 enzyme, which in turn helped to establish a structural basis of inhibition of mycobacteria. The results of present study clearly indicate the identification of some novel, selective and specific inhibitors against MTB that can be explored further for potential antitubercular drug.

Synthesis of novel triazole-incorporated isatin derivatives as antifungal, antitubercular, and antioxidant agents and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Nawale, Laxman; Arkile, Manisha A.; Sarkar, Dhiman; Shingate, Bapurao B. (Journal of Heterocyclic Chemistry, 2017)
A library of 1,2,3-triazoles efficiently prepared via click chemistry and evaluated for their antifungal, antitubercular, antioxidant, cytotoxicity, molecular docking and ADME prediction.

Facile and solvent-free domino synthesis of new quinolidinyl-2,4-thiazolidinones: antifungal activityand molecular docking - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Tupe, Santosh G.; Deshpande, Mukund V.; Khedkar, Vijay M.; Jha, Prakash C.; Shingate, Bapurao B. (Mini-Reviews in Medicinal Chemistry, 2018)
Objective: We have synthesized new quinolidinyl-thiazolidinones via Knoevenagel condensation-alkylation reaction, catalyzed by [Et3NH][HSO4]. The present approach offers several advantages such as higher yields, eco-friendly reaction condition and economic availability of the catalyst. Method: The newly synthesized compounds were evaluated for their in vitro antifungal activity against six fungal strains. Some of the synthesized conjugates displayed good to moderate antifungal activity. Conclusion: Again, the molecular docking study performed against the fungal sterol 14 alpha-demethylase (CYP51) showed an excellent binding affinity towards the enzyme which could rationalize the promising antifungal activity portrayed by these derivatives and provides a platform for structure based drug design.

Amide-linked monocarbonyl curcumin analogues: efficient synthesis, antitubercular activity and molecular docking study - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nagargoje, Amol A.; Akolkar, V. Satish; Bhansali, Sujit G.; Sarkar, Dhiman; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
An approach toward the synthesis of novel conjugates of 3,5-bis (arylidene)-4-piperidones (DAP) pharmacophore with amide-linkage has been developed via one-pot multicomponent reaction of aryl aldehydes, piperidinone and 2-chloro-N-phenylacetamide using [Et3NH][HSO4] as a catalyst/medium. Both substitutions on arylidene rings and piperidinone nitrogen (substituted 2-chloro-N-phenylacetamide) were varied. The synthesized conjugates were evaluated for their in vitro antitubercular activity against M. tuberculosis H37Ra (MTB) and M. bovis BCG strains. Among the series, compounds 4f, 4g, 4i and 4j showed remarkable broad spectrum antitubercular activity with low IC50 values. Furthermore, computer docking simulations, for the most active conjugates were performed with the active site of mycobacterial enoyl-acyl carrier protein reductase (InhA) support the antitubercular activity. Lower cytotoxicity, high potency and promising activity against MTB and M. Bovis BCG suggest that amide linked DAP could serve as good leads for further modifications and development.
Keywords: antimycobacterial activity; Bis (arylidene)-4-piperidones; Cytotoxicity; Ionic liquid; Molecular docking Study

[DBUH][OAc]-catalyzed domino synthesis of novel benzimidazole incorporated 3,5-Bis (Arylidene)-4-piperidones as potential antitubercular agents - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nagargoje, Amol A.; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
A series of new benzimidazole incorporated 3,5-bis (arylidene)-4-piperidones were synthesized by using aryl aldehydes, piperidinone, 2-(chloromethyl)-benzimidazole and DBU acetate [DBUH][OAc] act as a catalyst under solvent free condition in excellent yields. The synthesized compounds were screened for their in vitro antimycobacterial activity against M. tuberculosis H37Ra (MTB) and M. bovis BCG strains. The compounds 4a, 4b, 4e, 4i, 4k and 4l are highly potent against both the strains. Most of the active compounds are non-cytotoxic against MCF-7, A549, HCT 116 and THP-1 cell lines. Furthermore, a molecular docking study of these compounds was carried out to investigate their binding pattern with the target, active site of mycobacterial enoyl-acyl carrier protein reductase (Inh A). Therefore, these compounds can be subjected for further optimization and drug development which could give promising chemical leads for treatment of TB.
Keywords: Antitubercular activity; curcumin; Cytotoxicity; Ionic liquid; multicomponent reactions

Tetrazoloquinoline-1,2,3-triazole derivatives as antimicrobial agents: synthesis, biological evaluation and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Akolkar, Satish V.; Nagargoje, Amol A.; Khedkar, Vijay M.; Sarkar, Dhiman; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
In search of new active molecules, a small focused library of tetrazoloquinoline-based 1,2,3-triazoles has been efficiently preparedviaclick chemistry approach. Several derivatives were found to be exhibiting promising antimicrobial and antioxidant activity characterized by their lower minimum inhibitory concentration values. All the synthesized compounds exhibited excellent antibacterial activity against Gram negative bacteriaE. coliandF. devoransand antifungal activity againstC. albicansandA. niger. Further, these compounds were tested for their antitubercular activity against dormantMTB H37Raand dormantM. bovis BCGusing XRMA assay protocol and showed no significant activity. Also, the synthesized compounds were found to have potential antioxidant activity with IC(50)range = 12.48-50.20 mu g/mL. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against the active site of fungalC. albicansenzyme P450 cytochrome lanosterol 14 alpha-demethylase, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of thein vitroandin silicostudy suggest that the triazole-incorporated tetrazoloquinolines may possess the ideal structural requirements for further development of novel therapeutic agents.
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Docking study

[DBUH][HSO4]-catalyzed solvent-free synthesis of 1,5-benzodiazepine derivatives: bioevaluation and in silico molecular docking study - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nagargoje, Amol A.; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (Current Organic Chemistry, 2025)
Here, we report the solvent-free one-pot multicomponent synthesis of 4-substituted-1,5-benzodiazepine derivatives from O-phenylenediamine, aromatic aldehydes, and dimedone using [DBUH][HSO4] as a catalyst in excellent yields. This process was carried out in search of a reusable, easily accessible, affordable, and efficient catalyst. 1,5-Benzodiazepines demonstrate a new family of good inhibitors with potent anti-mycobacterial properties. The most promising compounds in the present series are 4c, 4i, and 4l which showed excellent activity and inhibited the growth of both MTB H37Ra and M. bovis BCG strains with lower MICs. The most active compounds were further studied for their cytotoxicity against cell lines MCF-7, A549, HCT116, and THP-1 by MTT assays and the compounds were found to be non-toxic. The fact that none of these compounds work against either Gram-positive or Gram-negative bacteria suggests that they are only effective against MTB. The in silico docking of the molecules against mycobacterial enoyl reductase, InhA enzyme could provide well-clustered solutions and have given valuable insights into the thermodynamic elements governing the binding affinities. The findings of this investigation unmistakably point to the discovery of extremely specific and selective MTB inhibitors, which can now be investigated further in search of possible anti-tubercular drugs.
Keywords: 1; 5-benzodiazepine; Antitubercular activity; Molecular docking; multicomponent reactions; [DBUH][HSO4]